Gender and the Integration of Newcomers in Merkel's Germany. Issue 1 (2nd January 2022) - MacRae, Heather
Abstract : In a stark departure from the historical stance that Germany is "not a country of immigration", Angela Merkel has made it a priority to welcome and integrate newcomers into German society. Over the course of her four terms, various Merkel-led governments have paid increased attention to the integration of newcomers, and specifically to the integration of women and girls. Drawing on key documents, including the four coalition agreements, I identify three different phases in the incorporation of gender into German integration policy. I also find evidence of several different, yet at times overlapping frames which shape the ways in which gender is framed into the integration discourse. Drawing on two case studies, I then draw attention to the fact that the shifts in discursive and policy frames at the federal level, are not immediately evident in policy initiatives as. As such, barriers to the integration of women and girls remain, even though Merkel has made this a central priority in her governments